Streamyx product: relationship between marketing mix strategy with sales improvement at business sales TM Melaka / Mohd Akmal Zubir - Zubir, Mohd Akmal (Faculty of Business and Management, 2008)
This research is about Department Business Sales TM Melaka. The purpose of this research is to figure out what are the factors relationships between marketing mix strategy with sales improvement. Streamyx product is the main factor of this study. Streamyx is a broadband access service which provides 'always on' connections to the Internet with bandwidth speeds from 384Kbps up to 2Mbps. With high-speed connectivity/bandwidth, the service is ideal to support most broadband applications such as web hosting, video streaming, e-commerce, distance learning and others. Business Sales main function is to market the products and services of Telekom Malaysia. Streamyx product that Business Sales provided has problem with their sales improvement since the competitors such as Celcom, Maxis and DiGi was establish in Melaka. Business Sales should compete and try to attract customers to buy streamyx product. The price for streamyx product in Business Sales is higher rather than the competitors' price. So that, it is difficult to BS to create their business opportunity cause by the price offered. Obviously ineffective promotion is one of the problems that Business Sales TM Melaka faces nowadays. Promotion activities about this streamyx product can contribute to the perception customers toward TM Melaka. Thus, Business Sales should think the best strategies and the best ways in order to solve all these problems. In that way, they can improve their sales improvement.